MULTIPLE CHOICE QUESTIONS
Question 1:
If (x + 1) is factor of the polynomial (2x2 + kx) then the value of k is
(a) –2
(b) –3
(c) 2
(d) 3
Answer 1:
(c) 2
Question 2:
The value of (249)2 – (248)2 is
(a) 12
(b) 477
(c) 487
(d) 497
Answer 2:
(249)2 – (248)2
We know
Hence, the correct answer is option (d).
Question 3:
If , where x ≠ 0 and y ≠ 0, then the value of (x3 − y3) is
(a) 1
(b) −1
(c) 0
(d)
Answer 3:
(c) 0
Thus, we have:
Question 4:
If a + b + c = 0, then a3 + b3 + c3 = ?
(a) 0
(b) abc
(c) 2abc
(d) 3abc
Answer 4:
(d) 3abc
Question 5:
If then the value of p is
(a) 0
(b)
(c)
(d)
Answer 5:
Hence, the correct answer is option (c).
Question 6:
The coefficient of x in the expansion of (x + 3)3 is
(a) 1
(b) 9
(c) 18
(d) 27
Answer 6:
(x + 3)3
So, the coefficient of x in (x + 3)3 is 27.
Hence, the correct answer is option (d).
Question 7:
Which of the following is a factor of (x + y)3 – (x3 + y3)?
(a) x2 + y2 + 2xy
(b) x2 + y2 – xy
(c) xy2
(d) 3xy
Answer 7:
(x + y)3 – (x3 + y3)
Thus, the factors of (x + y)3 – (x3 + y3) are 3xy and (x + y).
Hence, the correct answer is option (d).
Question 8:
One of the factors of is
(a) 5 + x
(b) 5 – x
(c) 5x – 1
(d) 10x
Answer 8:
So, the factors of are (5x + 1) and 10x
Hence, the correct answer is option (d).
Question 9:
If (x + 5) is a factor of p(x) = x3 − 20x + 5k, then k = ?
(a) −5
(b) 5
(c) 3
(d) −3
Answer 9:
(b) 5
Question 10:
If (x + 2) and (x − 1) are factors of (x3 + 10x2 + mx + n), then
(a) m = 5, n = −3
(b) m = 7, n = −18
(c) m = 17, n = −8
(d) m = 23, n = −19
Answer 10:
(b) m = 7, n = −18
Let:
Now,
(x + 2) is a factor of p(x).
So, we have p(2)=0
Now,
Also,
(x 1) is a factor of p(x).
We have:
p(1) = 0
By substituting the value of m in (i), we get n = −18.
∴ m = 7 and n = −18
Question 11:
104 × 96 = ?
(a) 9864
(b) 9984
(c) 9684
(d) 9884
Answer 11:
(b) 9984
Question 12:
305 × 308 = ?
(a) 94940
(b) 93840
(c) 93940
(d) 94840
Answer 12:
(c) 93940
Question 13:
207 × 193 = ?
(a) 39851
(b) 39951
(c) 39961
(d) 38951
Answer 13:
(b) 39951
Question 14:
4a2 + b2 + 4ab + 8a + 4b + 4 = ?
(a) (2a + b + 2)2
(b) (2a − b + 2)2
(c) (a + 2b + 2)2
(d) none of these
Answer 14:
(a) (2a + b + 2)2
Question 15:
(x2 − 4x − 21) = ?
(a) (x − 7)(x − 3)
(b) (x + 7)(x − 3)
(c) (x − 7)(x + 3)
(d) none of these
Answer 15:
(c) (x − 7)(x + 3)
Question 16:
(4x2 + 4x − 3) = ?
(a) (2x − 1) (2x − 3)
(b) (2x + 1) (2x − 3)
(c) (2x + 3) (2x − 1)
(d) none of these
Answer 16:
(c) (2x + 3) (2x − 1)
Question 17:
6x2 + 17x + 5 = ?
(a) (2x + 1)(3x + 5)
(b) (2x + 5)(3x + 1)
(c) (6x + 5)(x + 1)
(d) none of these
Answer 17:
(b) (2x + 5)(3x + 1)
Question 18:
(x + 1) is a factor of the polynomial
(a) x3 − 2x2 + x + 2
(b) x3 + 2x2 + x − 2
(c) x3 − 2x2 − x − 2
(d) x3 − 2x2 − x + 2
Answer 18:
(c) x3 − 2x2 − x − 2
Let:
By the factor theorem, (x + 1) will be a factor of f (x) if f (−1) = 0.
We have:
Hence, (x + 1) is not a factor of .
Now,
Let:
By the factor theorem, (x + 1) will be a factor of f (x) if f (1) = 0.
We have:
Hence, (x + 1) is not a factor of .
Now,
Let:
By the factor theorem, (x + 1) will be a factor of f (x) if f (1) = 0.
We have:
Hence, (x + 1) is a factor of .
Question 19:
3x3 + 2x2 + 3x + 2 = ?
(a) (3x − 2)(x2 − 1)
(b) (3x − 2)(x2 + 1)
(c) (3x + 2)(x2 − 1)
(d) (3x + 2)(x2 + 1)
Answer 19:
(d) (3x + 2)(x2 + 1)
Question 20:
If a + b + c = 0, then =?
Answer 20:
(d) 3
Thus, we have:
Question 21:
If x + y + z = 9 and xy + yz + zx = 23, then the value of (x3 + y3 + z3 − 3xyz) = ?
(a) 108
(b) 207
(c) 669
(d) 729
Answer 21:
(a) 108
Question 22:
If then (a3 − b3) = ?
(a) −3
(b) −2
(c) −1
(d) 0
Answer 22:
2 + b2 = ab
2 + b2 + ab = 0
Thus, we have:
No comments:
Post a Comment